Validation of Croatian Intelligibility in Context Scale - Tomić, Diana; Mildner, Vesna (2014)
Intelligibility in Context Scale (ICS - http://www.csu.edu.au/research/multilingual-speech/ics) is a parent report questionnaire assessing functional speech intelligibility of children. Among other languages, the ICS questionn aire has also been translated into Croatian. Similar questionnaire for kindergarten teachers has been developed in order to compare the assessment of children’s speech between the two groups of adults. Since ICS is a simple and easily administered tool, the report from both parents and teachers could be useful for kindergarten SLPs screening procedure. In this study, the speech of 486 preschool children (246M and 240 F) was assessed by both parents and teachers. Children were aged between 1 ; 2 and 7 ; 3 years. The mean value on the ICS for parents was 4.44 (SD = 0.59, minimum score = 2.42, maximum score = 5.00) and 4.52 for teachers (SD = 0.62 minimum score = 3.12, maximum score = 5.0). Parents’ ratings showed that by the age of three children’s speech is always (5) or usually (4) understood by family members and usually (4) or sometimes (3) by strangers. Although the overall results show that mean value of teachers’ assessment in the entire sample is higher, the results for younger children 1 ; 2-3 ; 0) are slightly lower. Older children are almost always (5) intelligible to their family members and usually (4) to strangers, reported by both parents and teachers. When compared, the results show that parents are more critical about the intelligibility of their three- and four-year olds being in the intensive period of speech sound development, while after the age of five there is no difference in the assessment of the two adult groups. Statistical analysis (descriptive statistics determining response frequencies for each of the seven items, tests of inter-item consistency, Cronbach’s alpha and factor analysis) for both questionnaires confirmed that the Croatian ICS is valid and internally reliable measure of the construct of functional intelligibility.
Projekt MZOS
Projekt MZOS
ENG